The effect of extracellular calcium elevation on morphology and function of isolated rat osteoclasts. Issue 6 (December 1989) - Datta, Harish K.; MacIntyre, Iain; Zaidi, Mone
Abstract : Osteoclasts are large multinucleate cells unique in their capacity to resorb bone. These cells are exposed locally to high levels of ionised calcium during the process of resorption. We have therefore examined the effect of elevated extracellular calcium on the morphology and function of freshly disaggregated rat osteoclasts. Cell size and motility were quantitated by time-lapse video recording together with digitisation and computer-centred image analysis. In order to assess the resorptive capacity of isolated osteoclasts, we measured the total area of resorption of devitalised cortical bone by means of scanning electron microscopy and computer-based morphometry. The results show that elevation of the extracellular calcium concentration causes a dramatic reduction of cell size, accompanied by a marked diminution of enzyme release and abolition of bone resorption. We propose that ionised calcium might play an important role in the local regulation of osteoclastic bone resorption.